2018
DOI: 10.1016/j.cub.2018.07.012
|View full text |Cite
|
Sign up to set email alerts
|

A Switch in Microtubule Orientation during C. elegans Meiosis

Abstract: In oocytes of many organisms, meiotic spindles form in the absence of centrosomes [1-5]. Such female meiotic spindles have a pointed appearance in metaphase with microtubules focused at acentrosomal spindle poles. At anaphase, the microtubules of acentrosomal spindles then transition to an inter-chromosomal array, while the spindle poles disappear. This transition is currently not understood. Previous studies have focused on this inter-chromosomal microtubule array and proposed a pushing model to drive chromos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
59
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 41 publications
(62 citation statements)
references
References 42 publications
2
59
1
Order By: Relevance
“…1 A) and transitions into a central spindle of microtubules between the segregated chromosomes in anaphase II ("maximal spindle shortening", Fig. 1 A) (Yang et al, 2003;Fabritius et al, 2011;Redemann et al, 2018). As one set of segregated chromosomes extrudes to generate a second polar body, the haploid, oocyte-derived pronucleus forms.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…1 A) and transitions into a central spindle of microtubules between the segregated chromosomes in anaphase II ("maximal spindle shortening", Fig. 1 A) (Yang et al, 2003;Fabritius et al, 2011;Redemann et al, 2018). As one set of segregated chromosomes extrudes to generate a second polar body, the haploid, oocyte-derived pronucleus forms.…”
Section: Resultsmentioning
confidence: 99%
“…As one set of segregated chromosomes extrudes to generate a second polar body, the haploid, oocyte-derived pronucleus forms. The spindle of microtubules elongate and dissipate as the oocyte-derived pronucleus forms (Yang et al, 2003;Fabritius et al, 2011;Redemann et al, 2018), but the mechanisms of remodeling and sealing the NE were not known.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…During C. elegans female meiosis, kinetochores disassemble in early anaphase I and appear to be dispensable for chromosome segregation (Dumont et al, 2010;Hattersley et al, 2016;McNally et al, 2016). In addition, tomographic reconstruction in electron microscopy of the C. elegans female meiotic spindle revealed that during anaphase I, central-spindle MTs transition from a lateral to an end-on orientation Redemann et al, 2018;Yu et al, 2019). Therefore, while the balance between central-spindle MTand kMT-driven forces may vary in different spindles, the former seems most important during female meiosis in C. elegans.…”
Section: Introductionmentioning
confidence: 99%